The MSME Activities of Amplang Process as a Learning Resource on Social Studies - Dona Eka Lovianie; Bambang Subiyakto; Rusmaniah Rusmaniah; M. Ridha Ilhami; Syaharuddin Syaharuddin (Universitas Lambung Mangkurat, 2023)
MSMEs are part of a productive economy carried out individually or as business entities and are not subsidiaries of companies, so that they can encourage economic growth in the country and the region. MSMEs in the field of Natural Resources (SDA) are one of the business sectors chosen by the community to start a business. The form of the MSME SDA sector is found in the Amplang business, namely its utilization in the aquatic sector in the form of fish as a raw material product. The activities in MSMEs processed in Amplang consist of production, distribution, and consumption, which can be used as social studies learning resources at the junior high school level. This study aims to discover how MSME activities are processed in Amplang, which can be used as social studies learning resources using a qualitative approach and descriptive methods based on economic activity theory. The results of this study state that processed fish SMEs are included in an economic activity covering aspects of production, distribution, and consumption that aim to create a product of use value, which can then be utilized in the world of education, namely as a learning resource developed in class VII material in economics learning. They are namely meeting the needs of the community, which contains sub-discussions regarding production, distribution, and consumption which are included in one economic concept, useful in forming the positive character of students as good citizens and the benefits of creativity in building entrepreneurship so that they can build knowledge about economic problems themselves as well as the community environment in the economic field through MSME activities.